The search for enhanced dielectric strength of polymer‐based dielectrics: A focused review on polymer nanocomposites. Issue 33 (21st May 2020) - Tan, Daniel Q.
Abstract: This report traces the leading scientific endeavors to enhance the dielectric strength of polymer dielectrics for energy storage and electrical insulation applications. Remarkable progress has occurred over the past 15 years through nanodielectric engineering involving inorganic nanofillers, coatings, and polymer matrices. This article highlights the challenges of dielectric polymers primarily toward capacitors and cable/wire insulation. It also summarizes several major technical approaches to enhance the dielectric strength of polymers and nanocomposites, including nanoparticle incorporation in polymers, filler‐polymer interface engineering, and film surface coating. More attention is directed to interface contributions, including rational design of core‐shell structures, use of low‐dimensional fillers and thermally conducting fillers, and inorganic surface coating of polymer films. These efforts demonstrated the enhancement in dielectric strength by 40–160% when controlling the fillers below 5 wt% in polyvinylidenedifluoride (PVDF) composites. This article also discussed the possible dielectric mechanisms and the positive role of interfaces against charge transport traps for attaining higher breakdown strength. The investigation of low‐dimensional filler/coating materials of high thermal conductivity can be key scientific subjects for future research. Abstract : This review traces the leading scientific endeavors to enhance the dielectric strength of polymer dielectrics for energy storage and electrical insulation applications. (a) The relationship between the thermal conductivity of insulating and conducting fillers and the dielectric strength improvement. (b) Effect of various technical routes including core‐shell, low‐dimension, thermally conducting and surface coating) on dielectric strength improvement of polymer dielectrics.